“Breaking barriers: empowering African youth through implementation of a therapeutic patient education program for juvenile idiopathic arthritis” - Hamdi, Wafa; Migowa, Angela; Lassoued Ferjani, Hanene; Fazaa, Alia; Faleye, Ayodele; Miladi, Saoussen; Maatallah, Kaouther; Ben Abdelghani, Kawther (Frontiers in Pediatrics, 2024)
Introduction: Patient education is crucial in managing chronic diseases like Juvenile Idiopathic Arthritis (JIA). Traditional methods such as videos and brochures often fail to maintain long-term knowledge retention. Therapeutic Patient Education (TPE) offers a more effective, patient-centered approach. Objective: PAFLAR aimed to implement a TPE program with a "train the trainers" masterclass to ensure effective delivery and improve outcomes for children with JIA. Methods: PAFLAR's TPE program was designed through a focus group, involving a literature review and strategic planning for the implementation step. The program includes specialized training for healthcare professionals enhancing their abilities to deliver TPE workshops. Participants were selected based on volunteerism and commitment to the project. Evaluations were conducted through feedback assessment of both patients and participants. Results: PAFLAR launched a TPE program in 2023, aimed at training healthcare providers to implement TPE effectively. This initiative included both in-person and virtual masterclasses, resulting in five workshops conducted in Kenya, Tunisia, and Nigeria. These workshops covered various aspects of JIA management, such as patient and family education, self-esteem, physical activity, treatment adherence, and pain management. Early results showed significant improvements in patients' and parents' understanding and management of JIA, with positive feedback indicating a need for further sessions. Conclusion: PAFLAR has taken the initial step in implementing a TPE program for JIA across three countries, representing different regions of Africa. The TPE program offers a promising alternative to traditional patient education methods, significantly improving patient care, empowering healthcare providers, and advancing healthcare systems.